Avaliação experimental de diferentes modos de operação de um biorreator de leito empacotado multicamadas para produção de celulases por cultivo em estado sólido - Rodrigues, Natalia Alvarez (2021)
In the last years, the interest in solid state fermentation (SSF) for the most diverse applications have been increased due to the possibility of using agro-industrial residues and the low generation of wastewater. The packed bed bioreactor (PBB) is one of the most commonly used equipment in these processes, however it presents problems in removing the metabolic heat generated. Another challenge is to carry these cultivations continuously. Thus, the main objective of the present work was to evaluate different modes of operation of a multilayer PBB applied in the production of endoglucanase by SSF. Initially, in plastic packings, the influence of temperature on the growth kinetics of the fungus Myceliophthora thermophila I-1D3b and an alternative method of inoculation through the mixture between fermented and non-fermented solids, called solid-solid inoculation, were evaluated. In experiments in the modular PBB, the effects of the flow configuration of water in the jacket and of the percolating air using the fungus Aspergillus niger C and of the modes of operation in classic batch, batch with movement and continuous, with M. thermophila as inoculum, were evaluated. At the end of all cultivations, extraction of soluble with distilled water was carried out and the endoglucanase activity was determined. The logistic equation fit well to the soluble proteins and endoglucanase activity profiles; the highest rate constants were observed at 45 °C. The solid-solid inoculation method proved to be experimentally feasible, although the yields of in terms of endoglucanase were lower compared to liquid inoculation with spore suspension. The cultivations in PBB showed that changing the fluid flow configuration, as well as the different modes of operation, did not influence on the maximum and average temperatures recorded throughout the cultivation, neither on the endoglucanase activity. In addition, in continuous operation the PBB behaved like a plug flow reactor and a steady state was achieved. It was also observed that in the continuous processes, the maximum CO2 production rate was 42% lower than in batches, indicating that in this operation mode there was a lower heat generation rate at the peak of growth. Therefore, the continuous operation mode proved to be applicable and advantageous for SSF processes in multilayer BLEs.